Potential biomarkers uncovered by bioinformatics analysis in sotorasib resistant-pancreatic ductal adenocarcinoma - Ramalingam, Prasanna Srinivasan; Priyadharshini, Annadurai; Emerson, Isaac Arnold; Arumugam, Sivakumar (Frontiers in Medicine, 2023)
Background: Mutant KRAS-induced tumorigenesis is prevalent in the lung, colon, and pancreatic ductal adenocarcinomas. For the past 3 decades, KRAS mutants seem undruggable due to their high-affinity GTP-binding pocket and smooth surface. Structure-based drug design helped in the design and development of first-in-class KRAS G12C inhibitor Sotorasib (AMG 510) which was then approved by the FDA. Recent reports state that the AMG 510 is becoming resistant in non–small-cell lung cancer (NSCLC), pancreatic ductal adenocarcinoma (PDAC), and lung adenocarcinoma patients and the crucial drivers involved in this resistance mechanism is unknown. Methods: In recent years, RNA Sequencing (RNA-seq) data analysis has become a functional tool for profiling gene expression. The present study was designed to find the crucial biomarkers involved in the Sotorasib (AMG 510) resistance in KRAS G12C mutant MIA-PaCa2 cells pancreatic ductal adenocarcinoma cells. Initially, the GSE dataset was retrieved from NCBI-GEO, pre-processed, and then subjected to differentially expressed genes (DEG) analysis using the limma package. Then the identified DEGs were subjected to protein-protein interaction (PPI) using the STRING database, followed by cluster analysis and hub gene analysis, which resulted in the identification of probable markers. Results: Furthermore, the enrichment and survival analysis revealed that the small unit ribosomal protein (RPs) RPS3 is the crucial biomarkers of AMG 510 resistance in KRAS G12C mutant MIA-PaCa2 cells pancreatic ductal adenocarcinoma cells. Conclusion: Finally, we conclude that the RPS3 is a crucial biomarker in Sotorasib resistance which evades apoptosis by MDM2/4 interaction. We also suggest that the combinatorial treatment of Sotorasib and RNA polymerase I machinery inhibitors could be a possible strategy to overcome resistance and has to be studied in In vitro and In vivo in near future.